Resorts as multifunctional recreation and tourism centers - Yavorska, V.; Molodetskyi, A.; Shashero, A.; Prykhodko, Z.; Nefedova, N. (Journal of Education, Health and Sport, 2023)
The article deals with the functioning of modern resorts as multifunctional recreation and tourism centers. Today, maintaining a healthy lifestyle has become a trend all over the world. As a result, traditional resort establishments are being modernized and provide the latest innovative wellness and spa services. Ukraine has a rich recreational potential to support existing and develop new resorts that can offer a variety of wellness treatments and leisure activities for various market segments.